MEMUTUS RANTAI KIMIAWI MENUJU KEMANDIRIAN EKOLOGIS PETANI PRAYUNGAN - M. Ruf'ul Athfal (LPPM Institut Pendidikan Nusantara Global, 2025)
Farmers in Prayungan Hamlet faced severe problems stemming from a dependency on chemical agriculture. This practice led to documented soil degradation and a drastic decrease in harvest yields, which fell from 45.5 tons in 2019 to 28.1 tons in 2021. The root problems identified included low farmer awareness, weak Farmer Group institutions and a lack supportive policies. This community service activity aimed to organize farmers using the Participatory Action Research method. The proposed solution involved a four part intervention strategy: (1) socialization and education, (2) strengthening Poktan institutional capacity, (3) practical training in producing alternative fertilizers, and (4) village policy advocacy. Key findings indicated a significant increase in farmer awareness and practical skills for producing fertilizer independently. The role of the Marsudi Farmer Group was succesfully transformed from merely a subsidy distributor into an active learning forum. Furthermore, the activity initiated a commitment from the Village Government to draft a Village Regulation supporting environmentally friendly agriculture. In conclusion, the PAR method proved effective in empowering farmers, which was confirmed by the independent adoption of these practices post-training.